The Role Of Japan In The Indonesian Economic - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSRACTS The role of Japan in the development of the h?dortesian economy fs Inevitably getting bigger Japan is the biggest market for Indonesian exports. As it does in exports, Japan is ars° the biggest sources of Import. From the hiiaterat sources of debts, if fs obi.tiotrs that Japan is also the biggest sources of loan In regard of getting the role of Japan, a certain kinds of awareness should be taken by the Japanese Goverrtment to lessen the negative feeling of the society that might rise to that which happened in 1974 will never rake place again